Border closures and the externalization of immigration controls in the Mediterranean: a comparative analysis of Morocco and Turkey. (6th September 2018) - Üstübici, Ayşen; İçduygu, Ahmet
Abstract: This article traces the recent history of border closures in Turkey and Morocco and their impact on human mobility at the two ends of the Mediterranean. Border closures in the Mediterranean have produced new spaces where borders are often fenced, immigration securitized, and border crossings and those facilitating border crossings criminalized. Here, bordering practices are conceptualized as physical bordering practices, border controls, and legal measures. Turkey and Morocco constitute comparable cases for an analysis of border closures insofar as they utilize similar mechanisms of closure, despite having quite different outcomes in terms of numbers. The article's findings are based on fieldwork conducted at both locations between 2012 and 2014, as well as on analysis of Frontex Risk Assessment Reports from 2010 to 2016. The first part of the article reflects on the concepts of border closure and securitization, together with their implications, and draws for its argument on critical security studies and critical border studies. The second part of the article is an overview of controls over mobility exercised in the Mediterranean from the 1990s onward. Then, in the third and fourth parts, we turn to the particular cases—respectively, Turkey and Morocco—in order to discuss their processes of border closure and the various implications thereof. Through analysis of the two country cases, we show that border closures are neither linear nor irreversible.